Association between reduced copy-number at T-cell receptor gamma (TCRγ) and childhood allergic asthma: a possible role for somatic mosaicism - Walsh, Kyle (2010)
Asthma is a chronic inflammatory disease of the lungs which affects more than 6.5 million American children. A family-based genome-wide association study of copy-number variation identified an association between decreased copy-number at TCRγ and childhood allergic asthma. TCRγ encodes the T-cell receptor gamma glycoprotein, a cell-surface protein found on T-cells and involved in cell-mediated immunity. Using quantitative real-time PCR, we sought to determine if copy-number variation at TCRα, TCRβ or TCRγ was associated with childhood allergic asthma in an independent cohort of 94 cases and 455 controls using DNA from buccal swabs. Copy-number variation at these loci is well-known, but appears to be dominated by somatic mutations. Genotyping results indicated that copy-number variants at these genes are largely somatic mutations, as inheritance did not show Mendelian consistency. In these mosaic cell populations, copy-number was significantly reduced among asthmatic children at TCRγ (p = 0.0199), but was not associated at TCRα or TCRβ (p = 0.7972 and 0.8585, respectively). These findings support the association between reduced copy-number at TCRγ and childhood allergic asthma. Further work is needed to resolve whether reduced copy-number at TCRγ predisposes individuals to asthma, or whether deletion of this gene is a somatic response to the disease.